Constraints analysis of Penaeus vannamei culture in Purba Medinipur district, West Bengal - Maity, Animesh; Saha, Biswarup; Roy, Aparna (Journal of the Inland Fisheries Society of India, 2021)
Penaeus vannamei farming is playing a pivotal role in the socio-economic development of India. India stands as the fifth-highest producer of shrimps. The state of West Bengal is the second largest shrimp producer amongst the shrimp farming states of India and contributed 1.23 lakh tonnes produce in 2017- 2018. A study was undertaken during 2019 in Contai-I, Deshopran, Contai-III, Chandipur block of Purba Medinipur district, West Bengal to analyze the constraints that prevailed in the P. vannamei culture. The study area was selected purposively and the 200 Penaeus vannamei farmers were selected using a simple random sampling method. Ex-post study was conducted with the help of a personal interview schedule aided with well structured and a pre-tested questionnaire consisting of 10 major domains of constraints. Garrett’s ranking technique was employed for allotment of ranking to various constraints. The results revealed constraints related to disease (rank 1) was opted as the major constraint, followed by other constraints related to marketing (rank 2), seed (rank 3), finance (rank 4), management practices (rank 5), natural hazards (rank 6), extension services (rank 7), labour availability (rank 8), input use (rank 9), and feed (rank 10). The results reflected the existing scenario of P. vannamei culture in the study area. Irrespective of the ranking of the various constraints, the majority of the constraints contributed to a setback of P. vannamei crop. The study suggested that the regulating agencies such as MPEDA and West Bengal Government may take appropriate remedial measures to combat the identified constraints for successful shrimp culture in the area.Key words Penaeus vannamei; constraints; farmers